2017
DOI: 10.1002/jum.14309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Combination of Strain and Shear Wave Elastography of Breast Masses for Differentiation of Benign and Malignant Lesions by Quantitative Assessment: Preliminary Study

Abstract: Objectives-To compare the diagnostic performance of strain and shear wave elastography of breast masses for quantitative assessment in differentiating benign and malignant lesions and to evaluate the diagnostic accuracy of combined strain and shear wave elastography.Methods-Between January and February 2016, 37 women with 45 breast masses underwent both strain and shear wave ultrasound (US) elastographic examinations. The American College of Radiology Breast Imaging Reporting and Data System (BI-RADS) final as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 46 publications
1
36
1
2
Order By: Relevance
“…Little published data pertaining to the direct comparison of diagnostic performance between strain and shear wave elastography in the same patients exists 11 , 12 , 14 . In this study, the difference in diagnostic performance was not significant when comparing conventional plus strain images and conventional plus shear wave images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Little published data pertaining to the direct comparison of diagnostic performance between strain and shear wave elastography in the same patients exists 11 , 12 , 14 . In this study, the difference in diagnostic performance was not significant when comparing conventional plus strain images and conventional plus shear wave images.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have compared strain and elasticity ratios, as determined by strain and shear wave elastography, of benign and malignant breast tumours in the same patients 11 , 12 . This study found the mean strain ratio and elasticity ratios to be significantly different between benign and malignant lesions in both strain elastography and shear wave elastography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these two studies used relatively different elastography techniques. Seo et al [12] reported similar diagnostic performances for both SWE and SE. In their study, the sensitivity of SR (95%) was higher than the mean elasticity (85%), and the specificity of the mean elasticity (96%) was higher than the SR (84%); however, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 87%
“…There are limited studies in the current literature investigating whether SWE or SE is more reliable in differentiating malignant and benign breast lesions [12][13][14][15]. The present study aimed to assess and compare the diagnostic efficacy of SWE and SE for the differentiation of benign and malignant breast lesions by applying both techniques on the same breast lesions.…”
Section: Introductionmentioning
confidence: 99%